IMPROVING STUDENT’S LEARNING LIVELINESS OF NATURAL SCIENCE BY GIVING QUESTION AND GETTING ANSWER STARTEGY AT ISLAMIC ELEMENTARY SCHOOL - Dian Andesta Bujuri; Baharudin Baharudin; Ida Fiteriani; Istiyani Istiyani; Masnun Baiti (JIP Jurnal Ilmiah PGMI, 2021)
The aim of this research is to determine the improvement of students' learning liveliness in natural science subject at class IV of state Islamic elementary school (MIN) by applying the Giving Question and Getting Answer learning strategy. The research approach of this research is classroom action research by three action cycles referring to the Kemmis and Mc. Taggart. The subject of this study is the students class IV at MIN 2 Bandar Lampung TA. 2018/2019 as many as 30 students. The data is collected through observation, interview, documentation, and test. Analysis of this study uses qualitative and quantitative data approaches. The research discovery proves that the GQGA strategy is able to improve the students’ liveliness and learning oucomet viewed by three aspects: cooperation, expressing opinion, and problem solving which an average of cycle I is 71.71%, cycle II is increase 82.18%, and cycle III also is increase 88.07% from the standard achievement 80%. Therefore, it can be concluded that the GQGA strategy can improve the students’ learning liveliness in the natural science learning on the theme "caring for environment, the various jobs, and my hero".